Perceived Thermal Response of Stone Quarry Workers in Hot Environment - Dutta, Priya; Chorsiya, Varsha; Nag, Pranab Kumar (Frontiers in Sustainable Cities, 2021)
Introduction: Impact of heat on health of workers goes unrecognized by the virtue of the indispensable fact that every individual has varied perception and tolerance capacity. The present study determine the physiological signs with perceived subjective responses under the thermal stress. Materials and Methods: The study was spread on open field stone quarry workers (N = 934) during the summer (May to June), post monsoon (September to October), and winter (December to January). Results: In the summer months, dry bulb temperature range from 36.1 to 43.2°C and the distribution of Wet Bulb Globe temperature (WBGT) outdoor values were outlier-prone than normal distribution indicated heat vulnerability. The environmental effect on weighted average skin temperature (Tsk) local segmental Tsk and deep body temperature (Tcr) were greater than the effects that might be attributed to work severity. The tolerance time level in summer months (65 ± 13 min at WBGT 35 ± 2.3°C) was less than in other two season. About 85% of workers in summer, 68% in post monsoon and 79% in winter recorded working heart rate greater than 90 beats/min. Physiological and subjective responses to heat stress indicated that during summer month the workers complained of excessive sweating (93.5%), feeling of thirst/dry mouth (88.7%), elevated Core temperature (Tcr) (58.7%) and decreased working capacity (75.6%). The observation found that around 14% workers were vulnerable to heat stress and the workers had no knowledge to mitigate the heat related illnesses. Discussion and Conclusions: The stone quarry work as compared to other outdoor workers have environmental adversaries which becomes confounding variables in the study of such occupations. There was significant difference (p < 0.001) as far as the physiological and thermoregulatory responses were concerned in three different months of investigation.